Stanowisko patriarchy Jeremiasza II Tranosa wobec zmiany kalendarza przez Watykan - Andrzej (Borkowski), Ks. Archimandryta (Elpis, 2014)
Subject of the paper is a standpoint of ecumenical patriarch Jeremiah II Tranos on the change of calendar introduced by Vatican. Patriarch Jeremiah’s attitude in relations with the Roman Catholic Church has been similar to the earlier one concerning Protestants whohad attempted to attract Orthodox faithful through their far-flungactivities. Nevertheless the patriarch has managed to maintain friendly relations with both denominations. His wisdom and discernment has helped to safeguard the Orthodox Church and the faith against foreigninfluence of the non-Orthodox who have pursued solely to ensure theirbenefits. Orthodox believers in Polish Republic have obediently followed his orders consistently rejecting any novelties and aberrations of the Latin Church who has not accepted a method of dialogue preferring to use calendar reform as a measure to apply papal propaganda. Initialfailure of the Vatican has not restrained its policy on Orthodoxy. Active and uncompromising proselyte activity of Jesuit order has repeatedly led to tensions and fights between faithful of both Churches. Initial trial to impose the new calendar has turned into battlefield of pressure and persecution. Orthodox people of the Polish Republic have protested against the new calendar treating it as one of the main reasons of their struggle. In such a particularly critical period in history ecumenical patriarch Jeremiah II Tranos has himself rushed to the aid of Kiev Metropolis located within boundaries of the Polish Republic. During his visit in 1588–1589 he solved many burning dilemmas.